2019
DOI: 10.3390/jcm8070970
|View full text |Cite
|
Sign up to set email alerts
|

High Constitutive Cytokine Release by Primary Human Acute Myeloid Leukemia Cells Is Associated with a Specific Intercellular Communication Phenotype

Abstract: Acute myeloid leukemia (AML) is a heterogeneous disease, and this heterogeneity includes the capacity of constitutive release of extracellular soluble mediators by AML cells. We investigated whether this capacity is associated with molecular genetic abnormalities, and we compared the proteomic profiles of AML cells with high and low release. AML cells were derived from 71 consecutive patients that showed an expected frequency of cytogenetic and molecular genetic abnormalities. The constitutive extracellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…This is mainly due to the expected and significant association between NPM1 mutations and morphological signs of differentiation (i.e., low frequency of FAB M0/M1 and high frequency especially of M4/M5; Fischer's exact test, p = 0.023) but one inv (16) patient with expected M4 morphology also contributed. Previous studies have also described an association between NPM1 mutations and morphological signs of differentiation and expression of the CD33 differentiation marker, as well as an inverse correlation with expression of the CD34 stem cell marker [34,35]. Thus, all observations described above are expected and can be explained by previously described characteristics of AML patient subsets in large AML studies.…”
Section: Aml Patients Included In the Studysupporting
confidence: 62%
See 1 more Smart Citation
“…This is mainly due to the expected and significant association between NPM1 mutations and morphological signs of differentiation (i.e., low frequency of FAB M0/M1 and high frequency especially of M4/M5; Fischer's exact test, p = 0.023) but one inv (16) patient with expected M4 morphology also contributed. Previous studies have also described an association between NPM1 mutations and morphological signs of differentiation and expression of the CD33 differentiation marker, as well as an inverse correlation with expression of the CD34 stem cell marker [34,35]. Thus, all observations described above are expected and can be explained by previously described characteristics of AML patient subsets in large AML studies.…”
Section: Aml Patients Included In the Studysupporting
confidence: 62%
“…Firstly, we previously compared the characteristics of patients selected according to these criteria (corresponding to approximately half of the consecutive patients), with the other patients without high peripheral blood blast counts during a defined time period, and we could not detect any significant differences with regard to karyotype or FLT3 mutations [56]. Secondly, in a previous study including 71 patients selected according to these criteria, we observed an expected frequency of various submicroscopic mutations in 54 genes frequently mutated in AML [12][13][14]34], that is also recognized in our present patient cohort (Table S1). Finally, our two patient subsets with and without relapse after completed intensive therapy are defined by very simple criteria, and the observation time used to define relapse-free patients is long.…”
Section: Discussionmentioning
confidence: 77%
“…With the advent of mass-spectrometry-based methods performed directly on human AML-sorted stem cells, a significant number of leukemia-specific proteins, especially membrane-associated, have been identified. The main objective of this approach has been the identification of novel AML stem cell biomarkers to exploit as immunotherapeutic targets, in order to eradicate the disease [182][183][184][185]. Moreover, patients' proteomic profiles could correlate with the mutational status and thus with the prognosis of AML patients, suggesting that proteogenomic approaches might become the main goal in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Cytogenetic and molecular genetic aberrations in AML have additional diagnostic and prognostic impacts [1,9]. Several strategies for subclassification, such as micro-RNA, epigenetic, transcriptomic, metabolomic, and proteomic characterization, have been suggested, although are currently not a part of routine handling of these patients [10][11][12][13][14][15]. Intensive chemotherapy is the only treatment that can cure AML, and autologous or allogeneic stem cell transplantation can be a part of this intensive treatment [3].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%